2009
DOI: 10.1021/ja8079143
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Nanostructuring on the Performance of Polymer/TiO2 Nanorod Bulk Heterojunction Solar Cells

Abstract: This work presents polymer photovoltaic devices based on poly(3-hexylthiophene) (P3HT) and TiO2 nanorod hybrid bulk heterojunctions. Interface modification of a TiO2 nanorod surface is conducted to yield a very promising device performance of 2.20% with a short circuit current density (J(sc)) of 4.33 mA/cm2, an open circuit voltage (V(oc)) of 0.78 V, and a fill factor (FF) of 0.65 under simulated A.M. 1.5 illumination (100 mW/cm2). The suppression of recombination at P3HT/TiO2 nanorod interfaces by the attachm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
209
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(215 citation statements)
references
References 34 publications
3
209
3
Order By: Relevance
“…They improved the power conversion efficiency from 0.35 to 0.6% with additional Ru-dye adsorbed at the TiO 2 interface measured at 1.5 AM but without reported illumination intensity. Lin et al reported the suppression of recombination at P3HT/TiO 2 nanorod interfaces by the attachment of Cu and Ru-dye species and an additional capping of the rods with anthracene-carboxylic-acid [11]. They even reached promising efficiencies of up to 2.2% at 1.5 AM and 100mW/cm [12,13], it is obvious why they perform differently when introduced in solar cell devices.…”
Section: Comparison Of Ptpa and P3ht Under Different Conditionsmentioning
confidence: 99%
“…They improved the power conversion efficiency from 0.35 to 0.6% with additional Ru-dye adsorbed at the TiO 2 interface measured at 1.5 AM but without reported illumination intensity. Lin et al reported the suppression of recombination at P3HT/TiO 2 nanorod interfaces by the attachment of Cu and Ru-dye species and an additional capping of the rods with anthracene-carboxylic-acid [11]. They even reached promising efficiencies of up to 2.2% at 1.5 AM and 100mW/cm [12,13], it is obvious why they perform differently when introduced in solar cell devices.…”
Section: Comparison Of Ptpa and P3ht Under Different Conditionsmentioning
confidence: 99%
“…Although power conversion efficiency (PCE) of polymer solar cells with these fullerene derivatives electron acceptors reached up to 9%, the complicated synthesis process and easy oxidation of fullerene in ambient still hinder their practical application [17][18][19][20]. Alternatively, inorganic nanocrystals such as CdSe, TiO 2 and ZnO can be used as electron acceptors combined with polymer donor in hybrid solar cells, which exhibit higher electron mobility and ambient stability with low cost [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The interfacial area between donor and acceptor can also be greatly enhanced by using a variety of solution processable polymers and nanostructured materials. 8 Extensive work has already been reported that has demonstrated the promise of combining conjugated polymers with various nanostructured inorganic materials, such as CdSe, 1,9,10 TiO 2 , [11][12][13][14] ZnO, 15,16 and Si. 17 In physically blended polymer-inorganic hybrid solar cells, although charge separation has been improved, 8,18 it is still difficult to control the composite morphology in order to provide an efficient charge transport via inorganic nanocrystals.…”
Section: Introductionmentioning
confidence: 99%